Academic Information System Islamic State University (UIN) Sunan Kalijaga Yogyakarta Android Based - Suryana Wijaya; Muhammad Dzulfikar Fauzi; Agung Fatwanto (IJID (International Journal on Informatics for Development), 2015)
The development of information systems is done so that the system gets better performance and is more in line with the wishes of users. However, until now there is no academic information system for UIN Sunan Kalijaga specifically developed based on mobile. In fact, mobile technology is currently growing very rapidly in Indonesia. Based on the Nielsen survey as of May 2011, the number of mobile device users in Indonesia reached 125 million out of the 238 million population. For this reason, it is necessary to develop the Academic Information System of UIN Sunan Kalijaga based on mobile, especially Android.The system development methodology used in this study is SDLC (Software Development Life Cycle). The steps are Analysis of system requirements, system design, and design, system implementation, testing, and evaluation.This research results an application that can be used to access academic information, such as schedule to attend the lecture, schedule of examination, card of yield study, presence and history of performance index. The special thing of this application is user still can see the academic information although offline with some condition.